Democracy and social cohesion in Perú: the promese and problem of Julio Cotler - Martín-Sánchez, Juan (Universidad Nacional del Litoral, 2019)
This article analyzes the intellectual career of Julio Cotler in its interaction with the notions of democracy and social cohesion. It argues that the intellectual fields of a specific society define and spread socio-political concepts according to the controversial intensity and the social sedimentation that these same fields entail. In some of his writings, Cotler explicitly referred to the relationship between democracy and social cohesion, but this concern also appeared in a more diffuse way in almost all his life work. Exploring Cotler’s role as a key intellectual in the Peru of the second half of the 20th century, this article focuses on three issues deeply embedded in his work: the historical argumentation, the indigenous question and the democracy. Inspired by R. Koselleck, U. Eco and P. Bourdieu, it examines some Cotler’s illustrating works and key arguments within the context of his broad intellectual production.